LEGAL PROTECTION FOR WORKERS GIG ECONOMY IN THE PLATFORM ECONOMY ERA - M. Alif Sannah Nurul Iqbal; Abdul Rokhim; Nofi Sri Utami (International Journal of Cultural and Social Science, 2025)
This research focuses on a juridical analysis of the conformity of Indonesia's labor law framework in providing protection for workers in the gig economy sector, particularly those working through digital platforms. The method used is normative juridical research with a legislative approach and literature study on legal literature, international reports, and relevant jurisprudence. The research results show that Indonesian labor regulations, such as Law Number 13 of 2003 and the Job Creation Law, have not been able to reach new forms of work relationships that are flexible but have a structural dependency on platform companies. The absence of formal legal recognition for digital workers has created a void in social and employment protections, and has strengthened the dominant position of corporations through opaque algorithmic regulations. The implications of these findings underscore the importance of reformulating labor laws to be more adaptive, substantive, and contextual, in order to ensure distributive justice and the rights of digital workers in the era of technology-based economies.